Ever the Teacher - Bowen, William G. (Book collections on Project MUSE., 1988)
In one of his commencement talks as President of Princeton University, William G. Bowen called upon the assembled graduates to find ways, in their lives, to blend ""the powers of the mind and the promptings of the heart."" This collection of his presidential writings--drawn from annual reports, opening exercises addresses, commencement remarks, and other speeches and essays--reflects a blend of analysis and advocacy that speaks both to public policy issues affecting all of American higher education and to the deeper meanings and values of Princeton. The writings selected for inc.